Implementation Pair Work and Storytelling in Teaching Speaking Fluency in Elementary School - Febyanti, Jihan Rizka; Sari, Dina Merris Maya (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
Fluency in English makes a great demand for teachers to start teaching English at the elementary school level. This study aims to examine how the application of paired learning and storytelling and their impact on students. The design in this research is using quantitative method. This study contains how students can interact, communicate and learn in class using pairing strategies and storytelling. The subjects of this study were teacher and students of elementary school. Researcher collects data by observing, interviewing, analyzing documents and communicating personally with teachers and students. The results of this study were applied by students filling out the answer sheets first to express their main ideas. Students will work in pairs and retell by storytelling. This will encourage students to speak. It was concluded in this study that students can speak about 110-113 words in every minute with a pause of about 1-3 seconds.